O processo de identificação profissional de futuros professores e sua relação com o saber: um olhar sobre os estágios supervisionados no ensino de Matemática (DMA/SC/UFS) - Oliveira, Mônica Teles Santos de (2020)
This work investigated the process of professional identification of future Mathematicsteachers and the Relationship with Knowledge, based on the experiences of thesubjectsparticipating in the research, when taking the Supervised Internships in MathematicsTeaching (ECS). It is a field research, under a qualitative approach with exploratoryandexplanatory purposes, driven by the following question: What are the implications of theECSand the actions experienced in this context, in the process of identification with theteachingprofession? To answer it, initially the study was based on texts by authors suchas Antunes(2007), Charlot (2000, 2005), Dubar (2005), Grillo and Gessinger (2008), Guimarães (2004),Nóvoa (1995, 2009), Souza (2009, 2015), Tardif (2002). Data were collected fromstudentsregularly enrolled in the Supervised Internship course in Mathematics TeachingIII inthesemester 2018/2, of the Mathematics Degree course at the Federal University of Sergipe(SãoCristóvão Campus), those who had already attended the others two mandatory internshipsinthat course. The main instruments of data collection were textual productionandsemi-structured interviews, in addition to the curricular menus of the referreddisciplines(ECS I; ECS II; ECS III). From the theoretical assumptions, the research showedthat theconstitution of professional identity refers to the dimensions of the RelationshipwithKnowledge developed by Charlot (2000). Thus, the epistemic, social and identitydimensionsrevealed themselves as constituents of the figure of the teacher built on the ideas of theseinterns and with the effect of their professional identification. In addition, the researchshowedthat mathematical knowledge, pedagogical knowledge and experiential knowledge constitutethe subjects' professional identity. The subjects considered that the ECS collaboratefortheappropriation of this knowledge and promote reflection on teaching, contributingtochangetheir perspective, from student to teacher, that is, collaborating with the professionalidentification process.